The Effect of Financing Maturity and Network Technology Infrastructure on the Digitalization of Hospital Management Information System - Windari, Adhani; Kismartini, Kismartini; Luqman, Yanuar; Wijanarko, Bagoes (Poltekita: Jurnal Ilmu Kesehatan, 2024)
The Hospital Management Information System (HMIS) is an integral information system used in hospitals, significantly impacting the performance of both service providers and patients. Enhancing the implementation of HMIS, particularly through system updates, can facilitate easier processes and access for patients and service providers. Digitalizing HMIS enables the production of highly useful information that can be more effectively shared among healthcare workers at all levels of the healthcare organization. The current study utilized a cross-sectional design, involving a sample of 639 hospital employees from various districts and cities in Indonesia. The independent variables examined were the maturity of financing and network technology, while the dependent variable was the digitalization of the HMIS. Data collection was conducted via a structured questionnaire, and the collected data were analyzed using a linear regression test. The analysis revealed that both financing maturity (b= 1.24; 95% CI= 0.59 to 1.89; p<0.001) and network technology infrastructure (b= 1.64; 95% CI= 0.96 to 2.33; p<0.001) had a significant positive effect on HMIS digitalization. These results underscore the importance of adequate financing and robust network technology in advancing the digitalization of HMIS. The findings suggest that hospital administrators should prioritize securing mature financing mechanisms and investing in advanced network technology infrastructure to enhance HMIS digitalization. Improved digitalization of HMIS can lead to better information sharing and coordination among healthcare providers, ultimately improving hospital performance and patient care.